Families making decisions : is there an Asian model? - Tan, Hwei Yong. (2008)
The primary purpose of this research is to measure spousal influence in family decision making situations in Singapore. More than a thousand responses were collected, from all three major races residing in Singapore and from families in various stages of the Family Life Cycle.